2020
DOI: 10.1007/s00109-020-01920-z
|View full text |Cite
|
Sign up to set email alerts
|

CU06-1004 (endothelial dysfunction blocker) ameliorates astrocyte end-feet swelling by stabilizing endothelial cell junctions in cerebral ischemia/reperfusion injury

Abstract: Cerebral ischemia, or stroke, is widespread leading cause of death and disability. Surgical and pharmacological interventions that recover blood flow are the most effective treatment strategies for stroke patients. However, restoring the blood supply is accompanied by severe reperfusion injury, with edema and astrocyte end-feet disruption. Here, we report that the oral administration of CU06-1004 (previously Sac-1004), immediately after onset of ischemia/reperfusion (I/R), ameliorated cerebral damage. CU06-100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…The distribution of the studies, according to the pathological model, was as follows: eight studies on cerebral ischemia, mostly induced by cerebral artery occlusion [ 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], five studies in cerebral hemorrhage induced by different methods [ 40 , 41 , 42 , 43 , 44 ], five studies on TBI, mostly by controlled cortical impact (CCI) [ 45 , 46 , 47 , 48 , 49 ], three studies combining cerebral ischemia and AD [ 50 , 51 , 52 ], three studies on aging [ 53 ] or AD models, using either amyloid-β (Aβ) [ 54 ] or transgenic animals [ 55 ], two studies on the experimental autoimmune encephalomyelitis (EAE) animal model for MS, induced by immunization with myelin oligodendrocyte glycoprotein (MOG) [ 56 , 57 ], three studies on status epilepticus (SE), induced with lithium chloride (LiCl)/pilocarpine or kainic acid (KA) treatment [ 58 , 59 , 60 ], five studies using diverse pharmacological or toxicological agents such as 3,4-methylenedioxymethamphetamine (MDMA), methamphetamine (METH), 3-chloro-1,2-propanediol, LPS, and glutaric acid (GA) [ 61 , 62 , 63 , 64 , 65 ], two studies involving pathogen-induced diseases, one in toxoplasmosis and another in human immunodeficiency virus (HIV) [ 66 , 67 ], one study which induced cognitive dysfunction by laparotomy [ 68 ], and one study which used the platelet-derived growth factor receptor β (PDGFRβ) +/− knockout model [ 69 ]. The three studies that combined stroke and AD were assigned to an independent category rather than being included in either stroke or AD categories.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution of the studies, according to the pathological model, was as follows: eight studies on cerebral ischemia, mostly induced by cerebral artery occlusion [ 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], five studies in cerebral hemorrhage induced by different methods [ 40 , 41 , 42 , 43 , 44 ], five studies on TBI, mostly by controlled cortical impact (CCI) [ 45 , 46 , 47 , 48 , 49 ], three studies combining cerebral ischemia and AD [ 50 , 51 , 52 ], three studies on aging [ 53 ] or AD models, using either amyloid-β (Aβ) [ 54 ] or transgenic animals [ 55 ], two studies on the experimental autoimmune encephalomyelitis (EAE) animal model for MS, induced by immunization with myelin oligodendrocyte glycoprotein (MOG) [ 56 , 57 ], three studies on status epilepticus (SE), induced with lithium chloride (LiCl)/pilocarpine or kainic acid (KA) treatment [ 58 , 59 , 60 ], five studies using diverse pharmacological or toxicological agents such as 3,4-methylenedioxymethamphetamine (MDMA), methamphetamine (METH), 3-chloro-1,2-propanediol, LPS, and glutaric acid (GA) [ 61 , 62 , 63 , 64 , 65 ], two studies involving pathogen-induced diseases, one in toxoplasmosis and another in human immunodeficiency virus (HIV) [ 66 , 67 ], one study which induced cognitive dysfunction by laparotomy [ 68 ], and one study which used the platelet-derived growth factor receptor β (PDGFRβ) +/− knockout model [ 69 ]. The three studies that combined stroke and AD were assigned to an independent category rather than being included in either stroke or AD categories.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies conducted on different stroke or ischemia animal models met the inclusion criteria and were incorporated in this systematic review. Two articles used a permanent middle cerebral artery occlusion (MCAO) model (one with direct injury [ 30 ] and the other with ferric chloride [ 34 ]), while five induced transient ischemia (four in the middle cerebral artery [ 35 , 37 , 38 , 39 ] and one in both common carotid arteries [ 36 ]). Transient ischemia times ranged from 15 min to 90 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…F-actin is the main cytoskeletal protein involved in cellular contraction, which is important for maintaining normal morphology and function (Deng et al, 2018). LIRI induces degradation of tight junctions by downregulating ZO-1 and VE-cadherin while stress fibers accumulate, compromising the endothelial barrier (Kim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the astrocytic morphology might resemble the one in Alzheimer's disease if there is progress to dementia. Studies have showed that there are reductions in astrocytic GLUT1 and lactate transporters, as well as retraction of astrocyte end‐feet and swelling consistent with neurovascular uncoupling, preceded wide‐spread β‐amyloid plaque pathology (Kim et al, 2020; Merlini et al, 2011). In addition, astrocytosis and subsequent glial scar formation has been shown in mice to functionally protect the brain from inflammation and infarct spread in brain ischemia (L. Li et al, 2008).…”
Section: Rare Neurological Conditions In Which Astrocytic Manifestation and Function Have Been Reportedmentioning
confidence: 99%